Development of cutting force database in machining S45C for monitoring the status of cutting tool wear - Fatin Nasha Izaty Mohd Nasir,; Ulul Azmi,; Haniff Abdul Rahman,; Mohd. Zaki Nuawi,; Muhammad Rizal, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The process of machining involves the removal of metal from the work material using one or more cutting tool and depending on the type of machine and machining process such as turning, milling, or grinding processes. These are the major machining processes in the manufacturing industry. In this study, a turning process of S45C carbon steel work material was conducted using a carbide cutting tool. Due to its desirable characteristics in term of qualities and affordable for mass production, S45C material is frequently used in the industry to produce automotive components. The focus of this study was to develop a database for monitoring the condition of the cutting edge during the machining operation by referring to the cutting force and the average of flank wear land (VB) at the cutting edge. The machining process was conducted in a dry condition without lubricants or coolants. The machining parameters used were cutting speed, V = 200 m/min, feed rate, f = 0.2 mm/rev, and depth of cut, d = 0.25 mm. The machining condition chosen in this study is similar with the machining condition used in the industry for machining S45C. The machining results found that the tool life was 119 minutes at flank wear, Vb = 0.3 mm. The relationship between cutting force and flank wear has been developed to establish a database based on the 2D I-Kaz coefficient. The 2D I-Kaz coefficient is then used for the purpose of monitoring and predicting the status of the cutting tool condition in the next machining process. The online monitoring of the cutting tool condition is expected to be able to control the quality of the components produced as well as to ensure that only worn-out cutting tool is replaced.